Direct Comparison of Flow-FISH and qPCR as Diagnostic Tests for Telomere Length Measurement in Humans - Gutierrez-Rodrigues, Fernanda; Santana-Lemos, Bárbara A.; Scheucher, Priscila S.; Alves-Paiva, Raquel M.; Calado, Rodrigo T. (PloS one, 2014)
Telomere length measurement is an essential test for the diagnosis of telomeropathies, which are caused by excessive telomere erosion. Commonly used methods are terminal restriction fragment (TRF) analysis by Southern blot, fluorescence in situ hybridization coupled with flow cytometry (flow-FISH), and quantitative PCR (qPCR). Although these methods have been used in the clinic, they have not been comprehensively compared. Here, we directly compared the performance of flow-FISH and qPCR to measure leukocytes' telomere length of healthy individuals and patients evaluated for telomeropathies, using TRF as standard. TRF and flow-FISH showed good agreement and correlation in the analysis of healthy subjects (R(2) = 0.60; p<0.0001) and patients (R(2) = 0.51; p<0.0001). In contrast, the comparison between TRF and qPCR yielded modest correlation for the analysis of samples of healthy individuals (R(2) = 0.35; p<0.0001) and low correlation for patients (R(2) = 0.20; p = 0.001); Bland-Altman analysis showed poor agreement between the two methods for both patients and controls. Quantitative PCR and flow-FISH modestly correlated in the analysis of healthy individuals (R(2) = 0.33; p<0.0001) and did not correlate in the comparison of patients' samples (R(2) = 0.1, p = 0.08). Intra-assay coefficient of variation (CV) was similar for flow-FISH (10.8 ± 7.1%) and qPCR (9.5 ± 7.4%; p = 0.35), but the inter-assay CV was lower for flow-FISH (9.6 ± 7.6% vs. 16 ± 19.5%; p = 0.02). Bland-Altman analysis indicated that flow-FISH was more precise and reproducible than qPCR. Flow-FISH and qPCR were sensitive (both 100%) and specific (93% and 89%, respectively) to distinguish very short telomeres. However, qPCR sensitivity (40%) and specificity (63%) to detect telomeres below the tenth percentile were lower compared to flow-FISH (80% sensitivity and 85% specificity). In the clinical setting, flow-FISH was more accurate, reproducible, sensitive, and specific in the measurement of human leukocyte's telomere length in comparison to qPCR. In conclusion, flow-FISH appears to be a more appropriate method for diagnostic purposes.